MODERN METHODOLOGICAL APPROACH TO THE FORMATION OF CREATIVITY SKILLS OF STUDENT YOUTH - Karabayeva Yodgoroy (Western European Studies, 2024)
This article highlights the modern methodological approach to the formation of the creativity abilities of student youth, as well as the scientific ideas of specialists on communicative competence, as well as the importance of forming communicative competence in students in professional educational institutions
Keywords: Creative thinking; education; technical support